ANALISIS PENENTUAN INFRASTRUKTUR PRIORITAS PADA KAWASAN KUMUH LINGKUNGAN KERANTIL KOTA BLITAR - Ashara Annas; Ria Asih Aryani Soemitro; Eko Budi Santoso (Journal of Civil Engineering, 2018)
Data update from Public Works and Housing Ministry records the existence of slum area in Kerantil District, Blitar City. Blitar City government has tried to address slum problem in that district, but until now slum improvement programs still not showing significant result. Based on the existing condition, research on priority infrastructure is conducted in Kerantil slum area, Blitar City. The aim of this research is to address proper program response for Kerantil slum area, Blitar City. This research begins with determining factors causing slum in Kerantil slum area using Confirmatory Factor Analysis. After the factors are determined, infrastructure response priority is determined by means of Service and quality (servqual) Analysis and Importance Performance Analysis (IPA) by comparing the level of importance and performance about infrastructure in slum area based on respondent answer. Several factors causing slum in that area are street infrastructure, drainage infrastructure, water infrastructure, waste infrastructure, building infrastructure, fire protection infrastructure, and green open space infrastructure. The other factors are government role, social, economy, society, and legality. The prioritized infrastructure in Kerantil slum area are waste infrastructure, fire protection infrastructure, and green open space infrastructure.